HISTORICAL LEGAL BASIS OF ADOPTION STAGES OF DEVELOPMENT - Dadaboeva Jumagul Anvarovna (Scholar Express Journals, 2023)
This article examines the historical stages of the legal basis of adoption based on Western and Eastern sources. Concepts such as the stages of the historical development of the legal basis of adoption, the requirements for adopters, the formalization of adoption, legal consequences, the rights and obligations of the adopter in relation to the adopted have been scientifically analyzed.
Keywords: Family; child; law